How Product Quality Drives Consumers to Speak: A Study on Word of Mouth - Gultom, Masrina; Asri, Wulandari; Pringgading, Elang (Yayasan Sinergi Kawula Muda, 2026)
This study aims to examine how product quality can encourage word of mouth (WOM) through purchase decisions and consumer satisfaction. In the context of increasingly complex business competition, understanding the effect chain from product quality to WOM is essential, especially for micro business actors such as local restaurants. This study uses a quantitative approach with accidental sampling techniques on 120 consumers of Mi Aceh Restaurant in Tebet, South Jakarta. The research instrument is in the form of a Likert scale questionnaire that measures four main variables: product quality, purchase decision, consumer satisfaction, and WOM. Data analysis was carried out using Path Analysis through SmartPLS 3 software. The results of the study show that product quality directly affects purchase decisions, purchase decisions affect consumer satisfaction, and consumer satisfaction affects word of mouth. The indirect influence of product quality affects word of mouth through purchasing decisions and consumer satisfaction. Maintaining and improving product quality is very important because it directly influences purchasing decisions, consumer satisfaction, and encourages positive word of mouth for restaurant businesses. Therefore, business actors need to ensure an easy and pleasant buying experience, as well as provide friendly and responsive services so that consumers feel satisfied and encouraged to recommend products voluntarily. The novelty of this research lies in identifying a serial mediation that links product quality, purchase decision, and consumer satisfaction to the emergence of positive word of mouth. In addition, this study was conducted within the context of traditional culinary micro‑businesses, specifically Mie Aceh, which has received limited academic attention, thereby offering new empirical contributions to the development of marketing strategies based on quality and consumer experience in the local culinary sector.